Performance evaluation in image processing with GAPP array processor - Navaux, Philippe O.A.; De Rose, César A.F.; Cavalheiro, Gerson G.H. (Microprocessing and microprogramming, 1995)
The application of parallelism considering the field of image processing is an alternative to implement real time image processing. The data parallelism found in array processors simplify the mapping of this kind of problem as each processing element works on part of the image. The GAPP board (Geometric Arithmetic Parallel Processor) is a near-neighbor mesh architecture with 144 processors interconnected as a 12 × 12 bidimensional array. This work analyzes the performance of the GAPP board regarding image processing. The implementation of two image convolution algorithms and the analyses of the obtained results, as well as the utilization of the GAPP board in this kind of application and the performance achieved are discussed. The results found in this work are also compared to the results presented in [11]. Some ways to achieve a better performance of the GAPP array in this kind of application are also presented.